2020
DOI: 10.48550/arxiv.2009.11520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proton size from precision experiments on hydrogen and muonic hydrogen atoms

D. Solovyev,
T. Zalialiutdinov,
A. Anikin

Abstract: The "proton radius puzzle" was recently solved by reducing the four-standard deviation discrepancy between the results for electronic hydrogen (H) and muonic hydrogen (µH) atoms to 3.3 value. The value of the root-mean-square radius of the proton (rp), extracted from experiments on measuring the one-photon 2s − 4p transition and the Lamb shift in hydrogen, is now 0.8335(95) fm, that is in good agreement with the muonic hydrogen experiments, 0.84087(39) fm. Even so, these values deviate significantly from the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…It is important to note that numerical values of NR corrections given by Eqs. ( 33)-( 36) are turned out several times less than the same NR corrections calculated recently in [13] for the other type of experiment monitoring the rate of 2s state quenching [8,9]. The difference with present results actually arises due to the rejected transiton matrix element of the emitted photon in the amplitude of scattering process used in [13].…”
Section: F=1contrasting
confidence: 88%
See 2 more Smart Citations
“…It is important to note that numerical values of NR corrections given by Eqs. ( 33)-( 36) are turned out several times less than the same NR corrections calculated recently in [13] for the other type of experiment monitoring the rate of 2s state quenching [8,9]. The difference with present results actually arises due to the rejected transiton matrix element of the emitted photon in the amplitude of scattering process used in [13].…”
Section: F=1contrasting
confidence: 88%
“…( 33)-( 36) are turned out several times less than the same NR corrections calculated recently in [13] for the other type of experiment monitoring the rate of 2s state quenching [8,9]. The difference with present results actually arises due to the rejected transiton matrix element of the emitted photon in the amplitude of scattering process used in [13]. It can be concluded that the detection of the excited ns/nd fraction of atoms via its fluorescence has a considerably higher potential accuracy than the experiments monitoring the rate of metastable state quenching [10].…”
Section: F=1mentioning
confidence: 51%
See 1 more Smart Citation
“…The excellent agreement of theoretical and experimental results up to this level is in some cases violated [13][14][15][16], which directs scientific attention to the verification of fundamental interactions, which, in turn, pursues the goal of eliminating such contradictions [17][18][19]. In such cases, a critical analysis of theoretical calculations of energies, fine structure, isotope shifts, etc is required for states in various atomic systems, revealing unresolved discrepancies with experiment, to determine fundamental constants or interactions [20], to set constraints to dark matter [21].…”
Section: Introductionmentioning
confidence: 99%

Thermal corrections for positronium

Solovyev,
Zalialiutdinov,
Anikin
2021
Preprint
Self Cite
“…transition frequencies in hydrogen [23], the correction equation ( 11) also does not depend on the angles between any pair of the vectors ν 3 , e 1 and e 2 . Therefore, the asymmetry of observed line profile cannot be eliminated by choosing 'magic' angles or experimental geometry as in [1,2].…”
mentioning
confidence: 99%